Subject Approach to Information Retrieval with Special Reference to Bengali Documents: A Critical Study - Halder, Sambhu Nath (International Journal of Knowledge Content Development & Technology, 2020)
The library provides its services to satisfy the user’s approach. This study was designed to assess users’ attitudes towards the retrieval of the Bengali document in OPAC through subject headings. This study contributes significantly to multi-lingual information retrieval. It also traces users’ perceptions regarding subject access highlighting the problems in the retrieval of Bengali documents by subject in OPACs. It can be inferred that some features are required to be incorporated to improve the functionality of the OPACs and thereby to satisfy users’ requirements. Results revealed that search experience using subject headings is not satisfactory. Where the “keywords” search rather performs better but due to redundancy of search, it is hard to retrieve required documents in the least possible time. It has also revealed that fewer perform known-item searches and their success rates for these searches are generally good. Thus, the findings demand standard principles and rules for the construction of Bengali Subject Headings. As per the need of new-age users, an efficient OPAC search facility can be developed where there will be a chance for ranking information retrieval. URL: http://ijkcdt.net/xml/24906/24906.pdf